IMPLENTASI PENDIDIKAN KARAKTER PADA MATA PELAJARAN AQIDAH AKHLAK DI MTS DARUSSALAM SENGKUBANG - Bahruddin, Bahruddin; Suhari, Suhari; Hamnah, Hamnah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This research departs from the phenomenon of the decline in the character of students in the world of education, this is evidenced by the indiscipline of students, lack of sense of responsibility, tolerance. Therefore, the character instilled through Aqidah Akhlak education to students needs to be pursued in order to apply it to everyday life. This research is a qualitative research. The research subject is the aqidah akhlak subject teacher at MTs Darussalam Sengkubang and the series of activities carried out. Data collection techniques using interviews with aqidah akhlak teachers, principals, curriculum sections, checking documents in the form of lesson plans and making observations in class IX accompanied by documentation. The results showed that: (1) the planning stage presents the process of preparing lesson plans and teaching materials. The lesson plans are made by including character values in them and will develop during the learning process according to the class situation. (2) the implementation stage presents the learning process, starting from learning steps, media and methods so that learning objectives can be achieved. (3) a complete explanation of the application of character values. (4) the assessment stage is carried out at the process stage, namely looking at the attitude of students during the process and the results stage, namely learning activities that spur on cognitive aspects, (5) the obstacles faced include the lack of student cooperation between teachers, students always return to the dormitory during class hours after breaks, lack of student awareness in conducting morning baiat ceremonies, (6) the solutions provided to overcome these obstacles by familiarising religious characters, reprimanding students if they make mistakes, giving sanctions to students so that they do not repeat them again, locking the dormitory so that no students return when the lesson is not finished, additional hours and remedials.